2021
DOI: 10.1158/2159-8290.cd-20-1500
|View full text |Cite
|
Sign up to set email alerts
|

MET Amplification Attenuates Lung Tumor Response to Immunotherapy by Inhibiting STING

Abstract: Immune checkpoint blockade (ICB) has revolutionized cancer therapy. However, the response of patients to ICB is difficult to predict. Here, we examined 81 patients with lung cancer under ICB treatment and found that patients with MET amplification were resistant to ICB and had a poor progression-free survival. Tumors with MET amplifications had significantly decreased STING levels and antitumor T-cell infiltration. Furthermore, we performed deep single-cell RNA sequencing on more than 20,000 single immune cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…The second way involves their immune suppressive properties, which may facilitate the persistence of oncogenic viruses like BPV and HPV and may also allow early neoplastic lesions to evade immunological surveillance and develop into overt cancers ( 27 ). Latorre and collaborators showed that ptaquiloside is able to inactivate natural killer (NK) cells ( 106 ), which are key players in innate immunity and are essential for defending the host against viral infections and against cancer ( 107 ). When activated, NK cells are able to recognize and destroy neoplastic cells and virus-infected cells.…”
Section: Bracken Fern and Bpv In Upper Digestive Carcinogenesismentioning
confidence: 99%
“…The second way involves their immune suppressive properties, which may facilitate the persistence of oncogenic viruses like BPV and HPV and may also allow early neoplastic lesions to evade immunological surveillance and develop into overt cancers ( 27 ). Latorre and collaborators showed that ptaquiloside is able to inactivate natural killer (NK) cells ( 106 ), which are key players in innate immunity and are essential for defending the host against viral infections and against cancer ( 107 ). When activated, NK cells are able to recognize and destroy neoplastic cells and virus-infected cells.…”
Section: Bracken Fern and Bpv In Upper Digestive Carcinogenesismentioning
confidence: 99%
“…Our study found HA mainly occurred in genes involved in the cell cycle and RTK-RAS-PI3K pathways, which are known to be involved in tumorigenesis. Previous studies have reported that amplifications of cell cycle driver genes and RTK-RAS-PI3K pathway genes, such as CCND1, MDM2, MET and VEGF-A, were associated with a lack of response to or poor survival benefit with anti-PD(L)-1 treatment [38][39][40][41][42][43][44]. In addition, reduced interferon response, low T cell abundance, poor T cell activity and a more immunosuppressive tumor microenvironment (enriched TGF-β signaling, hypoxia signaling) were observed in tumors with amplified genes in these two pathways, suggesting that hyperamplification in cell cycle/RTK-RAS-PI3K pathways may be a key point to drive anti-PD(L)-1 resistance through inducing both an immunosuppressive tumor microenvironment and malignancy hallmarks [40,41,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cGAS-STING signaling was demonstrated to be activated by DNA damage caused by ribonucleotide reductase regulatory subunit M2 (RRM2), which then suppresses malignant phenotype and improves radiosensitivity in LUAD 43 . Furthermore, a study showed that lung tumors with MET amplification can develop resistance to immune checkpoint blockade treatment through downregulation of STING expression 44 . In addition, Sex-determining region Y-related high-mobility group box 2 (SOX2) was found to occupy the cGAS promoter and repress its transcription, then dampen cGAS/STING signaling and ultimately inhibit ionizing radiation-induced anti-tumor immune responses in NSCLC 45 .…”
Section: Discussionmentioning
confidence: 99%